Molecular interactions of protein-based materials with ionic liquids - Muzammal, Shafaq (2021)
Renewable polymer resources have attracted an increasing amount of attention predominantly due to two major reasons, firstly environmental concerns, and secondly the realisation that our petroleum resources are finite. Silks and keratin-based materials such as wool are rich in protein content and have an immense importance as a renewable raw material in textile industry. Processing of such complex biopolymers has been hindered by the extremely low solubility in conventional organic solvents. Room temperature ionic liquids (RTILs) have shown favourable solvation properties for these materials and open up a wide possible range for application by turning them into novel structures and composites. In this work, molecular interactions of ionic liquids (ILs) with a range of amino acids (AAs) and peptides selected as model compounds were investigated through molecular dynamic (MD) simulations. The aim was to explain the underlying molecular mechanisms observed in the macroscopic processes with biotechnological relevance, such as, the dissolution of biomaterials in ILs, application of ILs in the separation and purification of amino acid molecules and other bioprocesses involving the replacement of organic solvents with ILs.